Dentifikasi Faktor-Faktor Penyebab Lunturnya Kearifan Lokal Masyarakat Dalam Melestarikan Hutan di Kenegerian Rokan Kecamatan Rokan IV Koto Kabupaten Rokan Hulu - Diana Gusti Rahayu; M. Mardhiansyah '; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Local wisdomis veryusefulasknowledgeof lifeas wellashuman behaviorin preservingenvironment. Local wisdomthatstillwalkingcanbe oneway ofpreventionagainstforest destruction.Asbe appliedsocietyat KenegerianRokanin preservingforest. This researchaimed to identifythe factors that causefadedoflocal wisdomatKenegerianRokan. The data had taken by using Snowball sampling technique which is twelve informan as a sample. Data were analized using Descriptif Analisis.Resultsshowed thatlocal wisdomthatno longer validamong themland distribution, banned of cutting down the main tree, levy fund, the banningcutting down treesinriversideareaandattitude ofhelping each otherin the making offield. The cause ofthe erosionlocal wisdominKenegerianRokancaused bywaninginstitutionalleaders, lack of development oflocal wisdom, the existenceof internalconflict, transmigrationprograms, development of technologyandconstruction ofroads andrapid economic development. Key word:local wisdom, fade, society, environmental sustainability.